2007
DOI: 10.1007/s11596-007-0103-4
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic effect of intercellular adhesion molecule-1

Abstract: ICAM-1 or Anti-ICAM-1 was substituted by PBS 5 muL on the day 10 or day 6 after incubation. Three days later, the CAMs were photographed in vivo, excised, sectioned and the number of microvessels was counted. In ICAM-1 group, there was increased number of microvessels arranged radially with "spoked-wheel" pattern around the gelatin sponges. The new microvessels growing perpendicularly to gelatin sponges were observed. The number of the microvessels growing in the CAM mesenchymes around the sponges in 3 subgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 5 publications
1
42
0
1
Order By: Relevance
“…It has been shown that angiogenesis induced in vivo in rat cornea and dependent on IL-4 and IL-13, is mainly mediated through a soluble VCAM-1/α4 integrin pathway [57]. In addition, ICAM-1 is capable to induce angiogenesis and to increase the survival of microvessels [58]. Increased amounts of VCAM-1 and ICAM-1 in RPM-cultures might support 3D formation of ECs exposed to the RPM.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that angiogenesis induced in vivo in rat cornea and dependent on IL-4 and IL-13, is mainly mediated through a soluble VCAM-1/α4 integrin pathway [57]. In addition, ICAM-1 is capable to induce angiogenesis and to increase the survival of microvessels [58]. Increased amounts of VCAM-1 and ICAM-1 in RPM-cultures might support 3D formation of ECs exposed to the RPM.…”
Section: Discussionmentioning
confidence: 99%
“…Ang-2 regulates TNF-␣-induced ICAM-1 expression on vascular endothelial cells and has a crucial role in the induction of inflammation (12). A previous study (10) has also shown that ICAM-1 induces angiogenesis and supports the survival of microvessels. However, the role of ICAM-1 in inflammatory lymphangiogenesis is poorly understood.…”
Section: Ang-2 Regulates Icam-1 Expression On Lecs Andmentioning
confidence: 91%
“…Grey relational analysis is an important part of the grey system theory. It is a system science theory put forward by the famous Chinese professor Deng Julong (1982) [40]. Here, grey refers to incomplete information, and the grey system is a system with incomplete information [41].…”
Section: Grey Relational Analysismentioning
confidence: 99%